2020
DOI: 10.3390/ijerph17051515
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the CMTM7 rs347134 Polymorphism with Dietary Patterns and the Risk of Obesity in Han Chinese Male Children

Abstract: A genome-wide association study (GWAS) in the Han Chinese population had found that single nucleotide polymorphism (SNP) on the CMTM7 gene rs347134 was significantly associated with Body Mass Index (BMI). In the present study, the association of the rs347134 SNP with obesity and its interaction with dietary patterns (DPs) were explored in Han Chinese children. This cross-sectional study group included 1292 children, in whom obesity-related indicators were evaluated, the rs347134 SNP was genotyped by improved M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
(61 reference statements)
0
5
0
Order By: Relevance
“… 2015 ; Zhu, Xue, Guo, Deng, et al. 2020 ). On the other hand, increased adherence to healthy dietary patterns rich in vegetables, fruits and whole grains was more likely to be associated with lower BMI or body fat (Barchitta et al.…”
Section: Resultsmentioning
confidence: 99%
“… 2015 ; Zhu, Xue, Guo, Deng, et al. 2020 ). On the other hand, increased adherence to healthy dietary patterns rich in vegetables, fruits and whole grains was more likely to be associated with lower BMI or body fat (Barchitta et al.…”
Section: Resultsmentioning
confidence: 99%
“…It is found that the expression of the Tuba1c gene, which promotes cell proliferation and regulates immune cell infiltration under inflammation conditions [ 34 35 ], was significantly distinguished in 5xFAD brain cortex. In addition, the expression of Cmtm7 , which is associated with immune B-cell antigen receptor regulation [ 36 ] and increased risk of obesity [ 37 ], was significantly distinguished in 5xFAD brain cortex. These findings suggest that the cerebral cortex in 5xFAD mice may accelerate immune cell infiltration and activate inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…DEGs were found to be enriched in reproduction, nuclear outer membrane-endoplasmic reticulum membrane network, identical protein binding, cell surface interactions at the vascular wall, cell adhesion, supramolecular complex, signaling receptor binding and extracellular matrix organization. CEBPB (CCAAT enhancer binding protein beta) [38], ACSL4 [39], MBD2 [40], ULK1 [41], NUCB2 [42], TWIST1 [43], HOOK2 [44], CLDN7 [45], TBK1 [46], YIPF6 [47], TFRC (transferrin receptor) [48], ENPP2 [49], SLIT2 [50], MFGE8 [51], FAT1 [52], GPC4 [53], COL6A3 [54], EGFL6 [55], AOC3 [56], CCN2 [57], LYVE1 [58], RARA (retinoic acid receptor alpha) [59], COL18A1 [60], THY1 [61], CD36 [62], PEMT (phosphatidylethanolamine N-methyltransferase) [63], AIF1L [64], OXTR (oxytocin receptor) [65], LMNA (lamin A/C) [66], CXCL14 [67], DKK3 [68], ANGPTL2 [69] and CMTM7 [70] were reported to be associated with obesity, but these genes might be linked with progression of GDM. AHR (aryl hydrocarbon receptor) [71], STS (steroid sulfatase) [72], PLAC1 [73], CYP11A1 [74], PSG11 [75], STAT5B [76], TLR3 [77], FOLR1 [78], HSPB1 [79], HSP90AA1 [80], ANXA4 [81], ATF3 [82], DAPK1 [83], ENTPD1 [84], ABL1 [85], VSIG4 [86], CD99 [87], VWF (von Willebrand factor) [88], PODXL (podocalyxin like) [89], PDPN (podoplanin) [90], RND3 [91], VCAN (versican) [92], AXL (AXL receptor tyrosine kinase) [93], PIEZO1 [94], GAS6 [93], LAMA4 [95], CAV1 [96], DLL1 [97], CD44 [98], CD81 [99], SMAD3 [100], NES (nestin) [101], DCN (decorin) [102], AGTR1 [103], SLIT3 [104], B2M [105…”
Section: Discussionmentioning
confidence: 99%